2011
DOI: 10.1902/jop.2011.110075
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of 3‐Wall Intrabony Defects in Patients With Chronic Periodontitis With Autologous Platelet‐Rich Fibrin: A Randomized Controlled Clinical Trial

Abstract: Within the limits of the present study, there was greater PD reduction, PAL gain, and bone fill at sites treated with PRF with conventional open-flap debridement compared to conventional open-flap debridement alone. However, a long-term, multicentered randomized controlled clinical trial is required to know the clinical and radiographic effects of PRF on bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
176
2
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(204 citation statements)
references
References 41 publications
19
176
2
7
Order By: Relevance
“…These results are in concordance with those of the aforementioned studies. 36,37 Several studies 15,16,17,38 have examined the suitability of autologous PRF for treatment of human intra-bony defects and revealed that PRF improves clinical 15 and radiographical 15,16,17,38 parameters. However, in the present study, no statistically significant differences were observed between both groups, except for the significant CAL gain noted in the test group.…”
mentioning
confidence: 99%
“…These results are in concordance with those of the aforementioned studies. 36,37 Several studies 15,16,17,38 have examined the suitability of autologous PRF for treatment of human intra-bony defects and revealed that PRF improves clinical 15 and radiographical 15,16,17,38 parameters. However, in the present study, no statistically significant differences were observed between both groups, except for the significant CAL gain noted in the test group.…”
mentioning
confidence: 99%
“…Similar technique has been adopted in other studies (Sharma, 2011; Subbaiah 2011, Sollazzo et al2010).…”
Section: Discussion:-mentioning
confidence: 93%
“…Su uso en cirugía bucal y maxilofacial, implantología oral y en particular en periodoncia es una tendencia actual e interesante (2). Así pues, la FRP es un biomaterial manipulable, por lo que se puede adaptar sobre la superficie recortándola, es utilizada en procedimientos periodontales, incluyendo recesiones gingivales, aumento del piso sinusal y corrección de defectos intraóseos (3,4).…”
Section: Revisición De Literaturaunclassified